MEMBANGUN STRATEGI PEMASARAN UMKM KULINER KAJIAN FENOMENOLOGI ANGKRINGAN DI SURABAY - ALDO HARDI SANCOKO; Veronika Rahmawati (Jurnal Keuangan dan Bisnis, 2019)
The rise of culinary business in angkringan creates its own polemic at food and beverage industry in Surabaya. As the number of angkringan increases, the level of competition among these businesses increases as well. The founder of angkringan also faces hard competition to achieve sustainability in its business. A comprehensive strategy in competing is needed to stay afloat, one of them is a marketing strategy. Hence, qualitative phenomenology research on angkringan in Surabaya is needed to capture the real experience of the founder so as to conclude the appropriate marketing strategy for the angkringan. This research is aimed at SME food and beverage business in angkringan that provides effective marketing strategies for angkringan in Surabaya. This research conclude that the angkringan has few constraints such as minimal working capital, high level of business competition, low level of HR education, and HR hijacking by competitors. Few solutions of this constraints are comprehensive training, supply chain quality improvement, and making SOPs.